(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The paper substantiates a structural and functional model of integrated accounting and corporate reporting intended for implementation within an enterprise management information system. The relevance is driven by the convergence of Ukrainian accounting regulation with European requirements for sustainability reporting and assurance, which increases expectations regarding consistency, verifiability, comparability and timely availability of both financial and sustainability disclosures. The purpose is to translate external requirements into internal data rules, calculation procedures and control activities that ensure end to end traceability of indicators from primary business events to final disclosures. The study applies a systems approach, structural logical modelling and comparative analysis of regulatory and standard requirements to define model contours, information artefacts and process interfaces. The proposed model comprises interconnected regulatory, strategy process, data, digital, accounting reporting and control contours. The strategy process contour formalises the linkage between business model, objectives, risks and key indicators, including the documentation of double materiality assessment results, risk registers and responsibility assignment. The data contour specifies a unified glossary, metadata and master data management rules, source system mapping, and a controlled taxonomy for reporting tags; it also defines change management procedures, versioning and approval workflows for indicator methodologies. The digital contour describes integration mechanisms between operational systems, accounting modules and analytics layers, as well as role based access control and segregation of duties for data creation, validation and approval. The accounting-reporting contour aligns accounting entries, management calculations and sustainability metrics through reconciliation points and consolidation procedures, enabling consistent reporting across periods and organizational units. The control contour introduces a control matrix with preventive and detective controls, thresholds, exception handling, and logging requirements.